Handbook of research on industrial advancement in scientific knowledge - Diaz, Vicente González-Prida; Bonilla, Jesus Pedro Zamora (Advances in human and social aspects of technology book series., 2019)
In a society that praises and promotes technological advancement, it becomes increasingly essential to review the effects of such rapid technological growth. New high-tech advances need to be examined to determine what they mean to science, society, and industry along with the benefits and challenges they present. The Handbook of Research on Industrial Advancement in Scientific Knowledge addresses the intersection of technology and science where engineering considerations, mathematical approaches, and management tools provide a better understanding and awareness of Industry 4.0, while also taking into account the impact on current society. This publication identifies methodologies and applications related to decision making, risk and uncertainty, and design and development not only on scientific and industrial topics but also on social and ethical matters. It is designed for engineers, entrepreneurs, academicians, researchers, managers, and students.